Kálmán Barsy, un escritor húngaro en Puerto Rico - Laboncz, Zsuzsa (Acta Hispanica, 2012)
The name of this Hungarian-born, l^atin American writer may sound unfamiliar to us, Hungarian readers, but nowadays Kálmán Barsy is one of the most popular and highly recognised authors in America, whose very first novel was honored with the pri^e Casa de las Américas in 1982. His novels, short stories and essays have been published in several languages, but we can only read one of them in Hungarian. No doubt, this work occupies a very important place in our literature, as it is treating a less known subject, the story of the socalled second generation of the emigration. This second generation has only a few members like Kálmán Barsy, who shares his homeland memories, and the difficulties of the integration into a new and strange community. With this study I try to present not just his life and work, but also the way he describes the experience of an emigrant of the second generation.